2014
DOI: 10.1371/journal.pone.0087771
|View full text |Cite
|
Sign up to set email alerts
|

Incontinentia Pigmenti: Learning Disabilities Are a Fundamental Hallmark of the Disease

Abstract: Studies suggest that genetic factors are associated with the etiology of learning disabilities. Incontinentia Pigmenti (IP, OMIM#308300), which is caused by mutations of the IKBKG/NEMO gene, is a rare X-linked genomic disorder (1∶10000/20∶000) that affects the neuroectodermal tissues. It always affects the skin and sometimes the hair, teeth, nails, eyes and central nervous system (CNS). Data from IP patients demonstrate the heterogeneity of the clinical phenotype; about 30% have CNS manifestations. This extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…Until now the cognitive profile of 10 women affected by IP has been described (Pizzamiglio et al, 2014). From this sample of adults it emerged that 3/10 presented intellectual deficiencies and 7/10 had a normal development without any discrepancies between verbal and performance IQ.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Until now the cognitive profile of 10 women affected by IP has been described (Pizzamiglio et al, 2014). From this sample of adults it emerged that 3/10 presented intellectual deficiencies and 7/10 had a normal development without any discrepancies between verbal and performance IQ.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, neonates with cutaneous lesions, seizures and ocular abnormalities show more diffuse brain lesions, whereas neonates with mild cutaneous lesions and without neurological symptoms do not have any brain lesions. To our knowledge only Pizzamiglio et al (2014) have described the neuropsychological profile of this disease in a group of 10 women with IP. Their results showed that approximately 30% presented intellectual deficiencies and approximately 70% presented a normal development without any discrepancies between verbal and performance IQ.…”
Section: Introductionmentioning
confidence: 99%
“…CYLD, which can hydrolyze K63-linked or linear chain, acts on RIPK-1, NEMO, and TRAF2 [30][31][32]. USP2 is another DUB that also acts at the level of RIPK1 [33]. Finally, OTULIN has been shown to be a DUB with specific affinity for linear ubiquitin chains that counteracts LUBAC activity [34,35].…”
Section: The Tnf-r1 Signaling Pathwaymentioning
confidence: 99%
“…An attempt to treat one IP patient with glucocorticoid has been reported [32]. The cognitive function, especially learning ability, of IP patients can also be surveyed in order to propose some reeducational training [33].…”
Section: Treatmentmentioning
confidence: 99%
“…Morbidity and mortality essentially result from extracutaneous ophthalmologic and neurologic complications, the last affecting approximately 30% of patients [9].…”
Section: Introductionmentioning
confidence: 99%